Pengaruh Online Customer Review dan Online Customer Rating terhadap Keputusan Pembelian Secara Online - Mia Setia; Pradita Nindya Aryandha; Hapsari Dyah Herdiany Hapsari; Latifah Putranti (Akmenika: Jurnal Akuntansi dan Manajemen, 2023)
Technological developments in the business world and the COVID-19 pandemic that has hit the world in recent years have changed people's shopping habits, from what people used to shop offline to shop online. This led to a significant increase in transactions on the marketplace. One marketplace that is often used by people in Indonesia is Tokopedia. Tokopedia has become the most visited marketplace by Indonesians in the last three years. In the marketplace there is a menu of information regarding goods purchased from consumers and star ratings from consumers, the importance of a menu of information regarding items purchased from consumers and this star award can make it easier for consumers to make purchasing decisions in the marketplace. Seeing the importance of information from consumers and giving stars from these consumers, a study was conducted to determine the effect of online customer reviews and online customer ratings on purchasing decisions at Tokopedia.